Students` Islamic personality on amanah: a structural modelling approach - Tekke, Mustaffa; Ismail, Nik Ahmad Hisham; Adnan, Mohamad Azrien Mohamed; Othman, Noraini (UPM Press, 2015)
The purpose of this study is to investigate the factorial structure of the Ummatic Personality Inventory (UPI). One of the constructs in UPI, Amanah was measured to understand the relationship among the factors namely, Amar Maaruf, Nahi munkar, Accountability to Allah and Accountability to Society. The sample of this study was a group of female students (n= 287) in a government school. Data were analysed using the Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). The findings for the structural model revealed that Khalifah and Accountability correlated to the Amanah. The percentage of variance accounted for by the independent variable was 63% accordingly, which indicated a very good effect size. This reflects that accountability of people for enjoining good deeds is moderately related to accountability towards society. The act of forbidding evil has a strong direct effect on accountability towards Allah. Thus, more efforts should be put on educating students to forbid evil-doing (nahi munkar). In future, a deeper analysis of this nature could be made on the other two constructs of UPI.